A hierarchical Zn2Mo3O8 nanodots–porous carbon composite as a superior anode for lithium-ion batteries. Issue 60 (4th July 2016) - Zhu, Yanping; Zhong, Yijun; Chen, Gao; Deng, Xiang; Cai, Rui; Li, Li; Shao, Zongping
Abstract : A hierarchical Zn2 Mo3 O8 nanodots–porous carbon composite has been successfully synthesized via the ingenious combination of ion-exchange and molten salt strategies, and the composite exhibits remarkable performance as an anode material for lithium-ion batteries. Abstract : A hierarchical Zn2 Mo3 O8 nanodots–porous carbon composite has been successfully synthesized via the ingenious combination of ion exchange and molten salt strategies, and the composite exhibits remarkable performance as an anode material for lithium-ion batteries.